Implications of Syncretic Beliefs and Practices Amongst Christians in Ondo State Nigeria; With Special Reference to Christian Participation in the Aringinya Festival of Yoruba Speaking People of Ikare-Akoko (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This study assessed the implication of syncretic Beliefs and practices amongst Christians in Ondo State, Nigeria, with special reference to Christian participation in the Aringinya Festival of Yoruba-speaking People of Ikare-Akoko. A survey research design method was adopted for the study. The population of the study comprises all Christian members (Orthodox Church and Pentecostal Churches) in the Ikare local government councils of the state. The sample of the study comprised Christians living in Ikare Akoko. Out of all the registered Churches in Ikare, only twenty Churches would be made up of ten Orthodox Churches and 10 Pentecostal Churches in Ikare Akoko. Simple random sampling was used. The research instrument that was adopted for this study was a questionnaire. The instrument was face-validated by three experts, three from the Department of Arts and Religious Education of the University of Abuja. Since the three clusters contain non-dichotomously scored items, the internal consistency of the clusters was determined using Cronbach Alpha. The internal consistency reliability estimate yielded 0.90 and 0.85. The result obtained from the questionnaire was computed and analyzed using descriptive statistics. The study showed that the implication of syncretic practices among Yoruba Christians includes sins, death, eternal condemnation, spiritual blindness, separation, and sickness. The study also showed that Christians in Ikare Akoko are not allowed to participate, fund, or invite their friends to attend the Aringinya festival in Ikare Akoko in Ondo State, as established by the Bible. The study disclosed that Churches in Ikare Akoko can employ fasting and prayers, crusade/ revival, constant preaching of God’s words, preaching on Christian ethics, and showing of love and care strategies to reduce syncretic practices in the Churches and among Christians in Ikare Akoko of Ondo State.